2017
DOI: 10.1002/biot.201700205
|View full text |Cite
|
Sign up to set email alerts
|

Modular Organization of the Thermobifida fusca Exoglucanase Cel6B Impacts Cellulose Hydrolysis and Designer Cellulosome Efficiency

Abstract: The protein engineering of the modular arrangement of a key exoglucanase from a highly cellulolytic bacterium, Thermobifida fusca, served to explore and compare three major enzymatic paradigms for cellulose degradation. This approach revealed highly active chimaeric forms of the exoglucanase that act in synergy together with a potent endoglucanase in bifunctional enzymes or divalent pseudo-cellulosome-like complexes. Such engineered enzymes could be further integrated into larger enzymatic complexes, thereby p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…In the best examples, designer and biomimetic cellulosomes outperformed free enzyme systems by a factor of 2−5 depending on the specific system. 12,13 The synergistic effect is comparable to that for natural cellulosomes. 14 Assembling native cellulases on polymeric and inorganic particle surfaces is the most reported method to make biomimetic cellulosomes.…”
Section: Introductionmentioning
confidence: 63%
“…In the best examples, designer and biomimetic cellulosomes outperformed free enzyme systems by a factor of 2−5 depending on the specific system. 12,13 The synergistic effect is comparable to that for natural cellulosomes. 14 Assembling native cellulases on polymeric and inorganic particle surfaces is the most reported method to make biomimetic cellulosomes.…”
Section: Introductionmentioning
confidence: 63%
“…These results demonstrate that different interdomain orientations influence the activity of the CBM3-GH11-BeSS chimeras, and highlight the importance of component geometry in MFP design. Previous studies have shown that the effects of protein fusion can depend on the sequence in which the individual protein components are joined, for example variations in the order of the Thermobifida fusca exoglucanase Cel6B fusions with CBM2, CBM3 and L2 domains, together with variations in the interdomain linkers, resulted in differing catalytic efficiencies against insoluble cellulose substrates [47] . These efforts have contributed to the design of synthetic cellulosomes, where the recombination of the same subset of components in different constructs with alternative geometries has a significant effect on catalytic performance [31] , [47] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the effects of protein fusion can depend on the sequence in which the individual protein components are joined, for example variations in the order of the Thermobifida fusca exoglucanase Cel6B fusions with CBM2, CBM3 and L2 domains, together with variations in the interdomain linkers, resulted in differing catalytic efficiencies against insoluble cellulose substrates [47] . These efforts have contributed to the design of synthetic cellulosomes, where the recombination of the same subset of components in different constructs with alternative geometries has a significant effect on catalytic performance [31] , [47] . These studies, together with the findings in the current work demonstrate how scaffold protein design can control the distance and relative orientation of catalytic domains for the successful design of MFPs.…”
Section: Discussionmentioning
confidence: 99%
“…The readily available T. fusca genome sequence reveals that it has the capacity to express many enzymes useful for hydrolyzing biomass, including numerous cellulases, xylanases, and carbohydrate transporters for sugar uptake ( Lykidis et al, 2007 ). Many of these thermally stable enzymes have been heterologously expressed in alternative microbial hosts and analyzed for their applicability to biomass conversion ( Ghangas and Wilson, 1987 ; Ali et al, 2015 ; Klinger et al, 2015 ; Saini et al, 2015 ; Zhao et al, 2015 ; Setter-Lamed et al, 2017 ; Yan and Fong, 2018 ; Ali et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%